2020
DOI: 10.3390/mi11030255
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Dielectrophoretic Response of Different Candida Strains Using 3D Carbon Microelectrodes

Abstract: Bloodstream infection with Candida fungal cells remains one of the most life-threatening complications among hospitalized patients around the world. Although most of the cases are still due to Candida albicans, the rising incidence of infections caused by other Candida strains that may not respond to traditional anti-fungal treatments merits the development of a method for species-specific isolation of Candida. To this end, here we present the characterization of the dielectrophoresis (DEP) response of Candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The authors cited leakage of the intracellular ions due to the low conductivity medium; a challenge that the DEP community is still working to meet. While this study did not characterize cell parameters, Islam et al used 3D carbon microelectrodes to characterize unique trapping responses of various Candida fungal strains [98]. The significance here was the greatest differences in cell trapping across the strains occurred at higher frequencies, followed by minimal trapping (net zero force).…”
Section: Dep Characterization Methods and Parametersmentioning
confidence: 95%
“…The authors cited leakage of the intracellular ions due to the low conductivity medium; a challenge that the DEP community is still working to meet. While this study did not characterize cell parameters, Islam et al used 3D carbon microelectrodes to characterize unique trapping responses of various Candida fungal strains [98]. The significance here was the greatest differences in cell trapping across the strains occurred at higher frequencies, followed by minimal trapping (net zero force).…”
Section: Dep Characterization Methods and Parametersmentioning
confidence: 95%
“…The stabilized electrospun AuCl 3 /PAN nanofibres were carbonized in a horizontal tube furnace (Carbolite Giro) to obtain the template AuNP/carbon nanofibres. The carbonization recipe used in our work was adapted from a process popularly used in carbon microelectromechanical systems (C-MEMS) technology 76 80 . Briefly, the process involved three steps: heating from room temperature to 900 °C with a heating rate of 5 °C min −1 , dwelling at 900 °C for 1 h, and cooling down to room temperature with natural cooling.…”
Section: Methodsmentioning
confidence: 99%
“…This is promising in the species-specific separation of Candida cells for sample preparation toward the diagnosis of candida infection. Reprinted with permission from Islam et al ( 50 ), Copyright 2020 Multidisciplinary Digital Publishing Institute. (D) Rapid and continuous separation of 1 and 10 μm polystyrene microparticles using 3D carbon streaming dielectrophoresis.…”
Section: Carbon-electrode Dielectrophoresismentioning
confidence: 99%
“…Cell membrane potential differs with phenotype; therefore, phenotypical cell separation is possible using DEP. 3D carbonDEP was implemented for different strains of Candida to characterize the dielectrophoretic behavior of Candida cells ( 50 ). The three most common strains, C. albicans, Candida tropicalis , and Candida parapsilosis were investigated, which showed that the strains indeed showed different dielectrophoretic responses, as shown in Figure 2C .…”
Section: Carbon-electrode Dielectrophoresismentioning
confidence: 99%